2006
DOI: 10.1073/pnas.0607260103
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1, a cancer- and Parkinson's disease-associated protein, stabilizes the antioxidant transcriptional master regulator Nrf2

Abstract: oxidative stress ͉ PARK7 ͉ NQO1 ͉ Keap1 ͉ neurodegeneration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
637
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(679 citation statements)
references
References 45 publications
(48 reference statements)
23
637
3
2
Order By: Relevance
“…This suggests that DJ-1 does not function downstream of caspase-8 activation or its effector caspases and their substrates. It has been reported that DJ-1 inhibits apoptosis by regulating different transcription factors to modulate gene expression (Clements et al, 2006;Bretaud et al, 2007;Fan et al, 2008a;Vasseur et al, 2009;Foti et al, 2010). However, we observed that DJ-1 did not affect DR mRNA or protein levels in H1299 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This suggests that DJ-1 does not function downstream of caspase-8 activation or its effector caspases and their substrates. It has been reported that DJ-1 inhibits apoptosis by regulating different transcription factors to modulate gene expression (Clements et al, 2006;Bretaud et al, 2007;Fan et al, 2008a;Vasseur et al, 2009;Foti et al, 2010). However, we observed that DJ-1 did not affect DR mRNA or protein levels in H1299 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 54%
“…The levels of TRAIL receptors, including death receptors and decoy receptors, are closely related to apoptosis induced by TRAIL. Because DJ-1 can function in the nucleus to regulate transcription (Clements et al, 2006;Bretaud et al, 2007;Fan et al, 2008a;Foti et al, 2010), it is possible that DJ-1 regulates the TRAIL signaling pathway by influencing the expression of TRAIL receptors at the transcriptional level. We transfected H1299 cells with siNC or siDJ-1 and examined the mRNA levels of the four TRAIL receptors using reverse transcriptase-PCR.…”
Section: Dj-1 Does Not Function Downstream Of Caspase-8 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…This ameliorates the ROS accumulation of Aβ peptides (Eftekharzadeh et al 2010). Nrf2 has been stabilised by the building up of dysfunctional DJ-1, which prevents the association of Keap1 with Nrf2 and leads to the proteasomal degradation (Clements et al 2006). Collectively, the activation of Nrf2 could be a therapeutic target for AD, which will ameliorate this disease.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…DJ-1 was first identified by our group as a novel oncogene product [1] and was later found to be a causative gene product of a familial form of PD, PARK7 [2]. DJ-1 plays roles in transcriptional regulation [3][4][5][6][7][8] and anti-oxidative stress reaction [9][10][11][12], and loss of its function is thought to affect the onset of PD. DJ-1 has three cysteines at amino acid numbers 46, 53 and 106 (C46, C53 and C106, respectively).…”
Section: Introductionmentioning
confidence: 99%